MITIGASI BENCANA BERDASARKAN KEPERCAYAAN LOKAL Studi Kasus Kepercayaan Lokal Dusun Stabelan dalam Mitigasi Bencana Erupsi Gunung Merapi Tahun 2010 - , MOCHTAR HIDAYAT, Dr. Pujo Semedi H.Y, M.A. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Merapi mountain is the most active mountains in Indonesia, this mountain erupted an average of every four years. The Stabelan village is on trim of Merapi Mountain and one of the top villages in the Boyolali Region, in the hamlet has a strong belief related to the volcano, in the hamlet stabelanâs belive is closely related to the related mitigation system with the eruption of Mount Merapi, the belief that there is such mountain given to the grandparent trim so that they avoid the threat of eruption itself, besides silence without a sound in the event of an eruption where it is believed if they arer evacuated when the eruption of Merapi as mock rulers, whose voice is not allowed Kentongan or not acceptable to it shouted Merapi was erupting. Residents also have confidence in a tomb . The tomb is believed to be the forerunner of Hamlet Stabelan . The tomb was believed akanmelindungi residents of Merapi eruption by providing guidance in the form of a dream to one of the people who have no interest in it . If people are given a dream then the citizens will tell the other residents of the mouth of the mouth . Usually people will believe the dream and immediately hold salvation for the village so that they avoid disaster volcano . Sego mountain is there if society village Stabelan hold salvation for Mount Merapi . Merapi eruption in 2010 , Hamlet Stabelan no one died and hamlets they do not get significant damage . They assume if it is because they always carry the traditions and beliefs that have residents profess . However, if studied logic , Hamlet Stabelan on the slopes northwest blocked by lava dome . So most of the impact occurring is volcanic ash bursts that make their village safe from the dangers of the eruption .